Unraveling social and economic problems: what basics of critical thinking skills are needed? - Sri Utami, Wiwik; Kusaeri, Kusaeri; Ridho, Ali; Yusuf, Ahmad; Widodo, Bambang Sigit; Prastiyono, Hendri; Murtini, Sri (Institute of Advanced Engineering and Science, 2025)
Equipping knowledge and developing critical thinking skills about social and economic issues to students is important. This study aimed to analyze the ability of prospective students of Islamic State of Madrasah of Insan Cendekia (ISM-IC) to think critically about socioeconomic problems. This research reveals a critical thinking skills gap among prospective students of Madrasah Tsanawiyah/Islamic Junior High School (IJHS) and non-IJHS who participated in the national selection of new students (NSoNS). This study uses a cross-sectional survey approach with standard instruments from the NSoNS ISM-IC. Data was obtained from 1,832 participants in the social sciences group test, consisting of 1,197 people from IJHS and 635 from non-IJHS. Data analysis using R Programming, package ‘ggstatsplot’, and via Microsoft Excel. The result is: i) a gap in social studies scores between IJHS and non-IJHS students of -0.215, with the social studies scores of IJHS students lower than non-IJHS; ii) critical thinking skills are proven to have a very real impact on the occurrence of social studies score gaps, through the inability of students to answer the higher-order thinking skills (HOTs) category questions. This finding indicates the urgency of the education unit to provide nuanced literacy models and learning and HOTs to increase think of critic ability about socioeconomic matter.